Impact of Non-Monetary Factors on Employee Performance: A Case of Internet Service Provider Sector in Kathmandu Valley - Manandhar, Pranay; Uprety, Pravat (Journal of Business and Social Sciences Research, 2022)
This study examined the impact of non-monetary factors (training, organisational support, promotion, job security, co-worker incivility and job rotation) on employee performance in Internet Service Provider (ISP) firms. The study used an inferential research approach to analyse the impact of independent variables on dependent variable. A standardised questionnaire was surveyed on a sample of 200 ISP employees from the Kathmandu Valley. The results demonstrate that job security and co-worker incivility have statistically significant effects on employee performance, but the rest of the independent variables do not. Based on finding, it is recommended that more the job security, more the employee performance in company and reduction of co-worker incivility around organisation environment will help boost employee confidence and performance. Along with this, this research also showed area for refurnishing other variables like available training, organisational support, promotion facility and application of job rotation for creating more impact of it on employee performance.